(untitled) (LIS TODAY, 2021)
Electronic information resources now serve as important sources of information to undergraduate students in Nigerian universities. This study aims to investigate the usage of electronic information resources by academic staff of Kaduna State University, (KASU) Kaduna. Survey research method was adopted to carry out the study. Using the survey research approach, the simple random sampling was used to select participants among the academic staff in study institution. The instrument used for data collection was a structured questionnaire tagged usage of electronic information resources. A total of 74 questionnaires were administered, of which 54 were duly filled giving. The findings revealed that 100. % of the respondents had used electronic journal, with 70.3% of them being using them for the purpose of research and majority are frequently using electronic journals. The major electronic resources used by students were internet search engines and they use it for research.